Seryl-tRNA synthetases : enzymes with multiple personalities - Bilokapić, Silvija (Array, 2009)
Summary:Seryl-tRNA synthetases (SerRS) are essential enzymes responsible for aminoacylation of cognate transfer-RNAs (tRNAsSer) with serine, which is then incorporated into the proteins being synthesized on the ribosome. Although tRNA synthetases are usually a very conserved class of enzymes, phylogenic analyses revealed the existence of two distinct types of serine-charging enzymes; a standard or bacterial-type SerRS is found in the majority of organisms (prokaryotes, eukaryotes and archaea), while a highly diverged methanogenic-type SerRS is confined to the methanogenic archaea. We give a short overview on our recent biochemical and structural contributions to the understanding of different molecular mecha-nisms of tRNA serylation